Sharing scholastic life: What do children think about it? - Sánchez Vázquez, María José (2005)
In this article we present the results found in a descriptive- exploratory study, in which we investigated a group of scholar's (9 and 10 years old) conceptions of their classmates with psychological disorders at school. The answers of 90 students who belong to low and average socio- cultural level groups were analyzed. These groups were identified in relation to the parent's occupational category and educational level. The instrument elaborated to such aim was a semi- structured interview which included different aspects related to: which the most frequent problems are, how these problems are expressed at school, which their determinants are and the consequences for the children, as well as the their self referred knowledge of these problems.